Polynomial estimation method for PN sequence based on reliability accumulation - Song CHEN; Kai-zhi HUANG; Hua ZHAO (Tongxin xuebao)
The issues of insufficient efficiency and poor error-tolerance of current high-order polynomial estimation me-thods under error conditions were studied.By combining the iterative berlekamp-massey(BM)algorithm in GF(2)and the improved Chase algorithm,a novel algorithm based on reliability accumulation was proposed.The sequence soft infor-mation was mapped to sequence reliability as the input information of BM algorithm,and the corresponding output relia-bility of estimated polynomial was accumulated as the rule of correct polynomial.In order to improve the estimation pre-cision,the candidate reliability-accumulated polynomial set were reduced by the characteristics of primitive polynomial in GF(2).The simulation results show that the proposed method is irrelevant with the tapped number of ator poly-nomial,and has a good estimation performance to estimate 17-order polynomials when the sequence BER is 18%.